Uploading Food Photos Phenomena on the Instagram Platform in Yogyakarta and Kelantan - Arif Ardy Wibowo; Budi Irawanto; ‪Ana Nadhya Abrar (ETTISAL : Journal of Communication, 2023)
The phenomenon of uploading food photos is one of the new habits in the world of social media. The creators who upload the food photos have a purpose and convey a message through food photos. This research aims to understand the behavior of Instagram users and the goals to be achieved when uploading food photos on Instagram. The method used in this research is phenomenology, with informants using Instagram in Yogyakarta, Indonesia, and Kelantan, Malaysia, with a qualitative approach. The results obtained from this research are that Khalda, an Instagram user in Yogyakarta, Indonesia has the main goal to share and to be known as a food vlogger in the process of uploading food photos. Meanwhile, Zyed, a user from Kelantan, Malaysia, has the same goal, namely sharing photos of food but using the media as a means of expression. These two users have in common that they want to upload their best version of food photos without any hope of getting likes or comments on the upload. In addition, in sharing, there was no message or ideological perspective that the two sources wanted to include in the food uploads. The conclusion of this research shows that the experience of using Instagram from the two informants is divided into four categories: the purpose of posting, type of food, photo aesthetics, and places to eat. The experiences of these two samples show that Instagram is an Ocularcentrism medium that places the eye at the center of social media usage.